INFORMATION-SEEKING BEHAVIOUR OF INTERNATIONAL ISLAMIC UNIVERSITY MALAYSIA LAW FACULTY MEMBERS - Majid, Shaheen; Kassim, Gava Mugeraa (Malaysian Journal of Library and Information Science, 2000)
Adequate knowledge about the information needs and seeking behaviour of users is vital for developing library collections, services and facilities to meet their information needs effectively. The purpose of this study is to identify the information channels used by the International Islamic University Malaysia (IIUM) law faculty members, information sources preferred by them, methods employed for getting the needed information and their library use pattern. A questionnaire was distributed to 80 IIUM law faculty members and 66 filledin questionnaires were returned, giving an overall response rate of 82.5 percent. It was found that respondents used various sources for acquiring the needed information. Books were ranked as the most important source for teaching and research purposes, followed by law reports and statutes. Respondents preferred to first consult their personal collection before resorting to other information providing sources and agencies. The Online Public Access Catalogue (OPAC) and CD-ROM were the most frequently used IT-based sources and facilities. E-mail was the most popular among the Internet-based services and applications. On the whole, respondents perceived IIUM library collections, services and facilities as adequate to meet their information needs effectively.